Last one home - Macomber,Debbie (London Arrow Books, 2015)
"The Palmer sisters couldn't be more different. Karen, the eldest, is the responsible one the one who got the grades, married the perfect guy, and has two wonderful, high-achieving children. Cassie is the rebellious one, who got pregnant right after high school and married the wrong man, despite her family's misgivings. And Nicole is a free, creative spirit, who's always been indulged and pampered as the baby of the family who could do no wrong. These differences were enough to drive the three sisters apart over the years, but their mother's unexpected death makes them realize that she would have wanted them to repair old wounds and let bygones be bygones. What they discover is that none of their lives are as perfect as they seem, and despite their differences, they're the only family each other can depend on. A heartwarming illustration of all the ups and downs of life, and the sometimes fraught, but always enduring, relationship between sisters.